Women on the Margins of Imperial Plots: Farming on Borrowed Land - Podruchny, Carolyn; Thistle, Jesse; Jameson, Elizabeth (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2018)
Rather than provide a detailed discussion of the findings of Carter’s Imperial Plots, this essay explores the lives of three women at the edges of the processes Carter outlines to illustrate the widespread influence of the narrowing of women’s roles and how women resisted and adapted. Our portraits of Maxi’diwiac (Hidatsa), Nancy Arcand (Metis), and Frances Zatylny (Ukrainian-Canadian) show how their agricultural practices (and their lives more generally) were confined by colonialism, while farming became their major site of resistance. Carter’s detailed descriptions of the racialized and gendered spaces on the prairies uncovers the mechanism of colonialism and helps us understand how cultural, social, economic, and political forces shaped the structures in which these women could operate. Despite these women’s deep ties to and labour on their farms, they could not maintain ownership of them.